Reduction of inflammation and colon injury by a Pennyroyal phenolic extract in experimental inflammatory bowel disease in mice - Rocha, João (2019)
Purpose: Little is known about the pharmacological effects of the phenolic compounds of Pennyroyal (Mentha pulegium). This Mediterranean aromatic plant, used as a gastronomic spice and as food preservative by the food industry has been studied mainly due to its essential oil antibacterial properties, composed primarily by monoterpenes. With this work, we aimed to evaluate the effects of a phenolic extract of pennyroyal in the impairment of inflammatory processes in Inflammatory Bowel Diseases (IBD) and in the potential inhibition of progression to colorectal cancer (CRC). Methods: To that purpose, we evaluated the effect of pennyroyal extract administration in a model of TNBSinduced colitis in mice and further determined its effect on human colon carcinoma cell proliferation and invasion. Results: The phenolic extract of pennyroyal exhibited antioxidant properties in in vitro assays and administration of the extract in a rat model of carrageenan-induced paw oedema led to significant anti-inflammatory effects. Further results evidenced a beneficial effect of the phenolic extract in the attenuation of experimental colitis and a potential antiproliferative effect on cultured colon cancer cells, effects not previously described, to our knowledge. A reduction in several markers of colon inflammation was observed following administration of the extract to colitis-induced mice, including functional and histological indicators. A successful inhibition of cancer cell invasion and proliferation was also observed in in vitro studies with HT-29 cells. Furthermore, the extract also led to a reduced expression of iNOS/COX-2 in the colon of colitis-induced mice, both being crucial mediators of intestinal inflammation. Conclusions: Taking into consideration the central role of inflammation in the pathophysiology of CRC and the recognised connection between inflammatory events and cancer, these results enlighten the relevance of the phenolic constituents of pennyroyal as important pharmacological sources in the investigation of new treatment options for patients with inflammatory bowel diseases